Restricting Free Speech: The Impact on Opposition Parties in Singapore - James Gomez (The Copenhagen Journal of Asian Studies, 2006)
Although there has been a great deal of publicity surrounding the restriction of free speech with regard to opposition parties in Singapore, in real terms, the value of free speech for such parties is limited. First, defamation laws in Singapore require the opposition parties to exercise extreme caution to ensure political comments do not result in costly defamation suits or even imprisonment. Second, free speech in itself is of limited use politically for opposition parties if the content of this speech is not disseminated widely by the local media. As a result, both the fear of legal suits and the limited dissemination of content continue to restrict the potential of free speech for opposition parties in Singapore. This means the contribution of free speech activities to inter-party debate is low in Singapore, thereby undermining the fundamental role of democracy premised on fair inter-party competition.